CHARACTERIZATION OF ROCK LAYERS BASED ON REFRACTION SEISMIC METHOD: A CASE STUDY OF MENTARANG’S HYDRO-POWER PLANT, MALINAU REGENCY, NORTH KALIMANTAN - Wisnu Slamet Priyanto; Jauhari Arifin (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2021)
North Kalimantan Province is a new province that is dynamic in development in order to prosper the inhabitants. The research and exploration to make a plan to develop new renewable energy are one of their main programs. The hydro-power plant of Mentarang, Malinau Regency, Kalimantan Utara is a plan program in 2020. The research study of hydro-power plants is essential as a reference in the development plan and avoids the hazard, miss calculation due to human error, etc. Seismic refraction is used in the feasibility study and detailed engineering study (FS DED) of Mentarang's Hydro-power plant. Analysis from the Seismic refraction method can be used as an input parameter for deciding the feasibility of Mentarang's hydro-power plant. This study aims to characterize the sub-surface layers, structure, and sub-surface layer thickness within this area. The seismic refraction method uses the intercept time or travel-time versus distance and processed using the reciprocal method, then it is modelled using inversion and resulted in a 2D profile. This research study was used the seismic refraction method with geometry acquisition of 14 sources with two spread and 5 meters of geophone interval.  The analysis result of the 2D inversion profile model, in general, is classified as four strata layers. These strata are categorized as weathered layers with 5-15 meters of thickness, clay, and Sandstone about 5-20 meter of layer thickness, Sandstone with the layer thickness of about 20-50 meters, and lastly, granite, lava rocks, or limestone with depth more than 70 meters below the subsurface. There is a possibility of a structure at an offset of 70 meters, but this method's limitation will overestimate the conclusion. Therefore, it is necessary to bring another method that more sensitive to work further in research study evaluation of hydro-power plant Mentarang, Malinau Regency, North Kalimantan.